Gender differences in the influence of personality traits on spicy food liking and intake. (June 2015) - Byrnes, Nadia K.; Hayes, John E.
Highlights: Recently, we showed personality measures correlated with chili liking and intake. Here, we test if personality modifies relationships between burn intensity and spicy food liking. Limited moderation by personality were seen. Sensation Seeking mattered more in women; Sensitivity to Reward mattered more in men. Relationship between variables influencing liking and intake of spicy foods may differ between men and women. Abstract: It has been proposed, and only minimally explored, that personality factors may play a role in determining an individual's sensitivity to and preference for capsaicin containing foods. We explored these relationships further here. Participants rated a number of foods and sensations on a generalized liking scale in a laboratory setting; after leaving the laboratory, they filled out an online personality survey, which included Arnett's Inventory of Sensation Seeking (AISS) and the Sensitivity to Punishment and Sensitivity to Reward Questionnaire (SPSRQ). Recently, we reported strong and moderate correlations between the liking of a spicy meal and the personality constructs of Sensation Seeking (AISS) and Sensitivity to Reward (SPSRQ), respectively. Here, we use moderation models to explore the relationships between personality traits, perceived intensity of the burn of capsaicin, and the liking and consumption of spicy foods. Limited evidence of moderation was observed; however differential effects of the personality traits were seen in men versus women. In men, Sensitivity to Reward associated more strongly with liking and consumption of spicy foods, while in women, Sensation Seeking associated more strongly with liking and intake of spicy foods. These differences suggest that in men and women, there may be divergent mechanisms leading to the intake of spicy foods; specifically, men may respond more to extrinsic factors, while women may respond more to intrinsic factors.